Experiences in teaching new technologies in computer science university degrees - Queiruga, Claudia Alejandra
The digital technological era in which we live makes our students native technological users, which radically redefine the ways in which teaching and learning take place. In this context, the Computer Science School of the UNLP describes a discovery learning proposal for two mandatory subjects, Software Development Workshop1 and Software Laboratory2. The students in these subjects carry out projects related to local demands and the field of mobile applications, and are encouraged to form interdisciplinary aptitudes, owing to the emphasis that university education places in structural contents that have long term validity.